THE ANALYSIS OF NON-EQUIVALENCE TRANSLATION AT WORD LEVEL FOUND IN â€œI TUUNG KUNINGâ€ TALE - I Nyoman Rajin Aryana (Politeknik Negeri Bengkalis, 2018)
AbstractÂ Â Â Â Â Â Â Â Â Â Â This paper was aimed at analyzing the non-equivalence translation at word level from the Balinese Tale entitles â€œI Tuung Kuningâ€ written by I Gusti Made Sutjaja. The tale was written in Balinese then translated into Indonesian and English. From the English translation itself the non-equivalence translation at word level observed. Then data was presented descriptively. The analysis proved that 3 problems of non-equivalence translation found in the tale, meanwhile there were 3 translation strategies applied in making the translation itself. The problems were: difference in expressive meaning, target language lacks a specific term (hyponym), and culture-specific concept. While strategies applied here were; translation by a more neutral or less expressive word, translation by cultural substitution, and translation by omission. Even though, non-equivalence translation was impossible to be avoided, the translator might prevent it by really understanding the culture aspects of both the source language and the target language.Â Keywords: translation, non-equivalence translation at word level, translation strategies,Â Â Â Â Â Â Â Â Â tale